Anatomical and physico-chemical changes in rastali banana (Musa aab rastali) during fruit growth and ripening. - Tee, Yei Kheng (2012)
A series of physico-chemical (physical, chemical and physiological qualities) and structural changes of Rastali banana were conducted on weekly intervals from the 1st until 12th weeks after emergence of the first hand in order to establish growth pattern and physico-chemical changes in Rastali banana during growth and development. Later, experiment was carried out to study the optimum harvest periods of Rastali banana based on the physico-chemical changes during ripening. For these purposes, Rastali bananas were tagged after the emergence of the first hand. Hands were numbered from the top of bunch to the bottom (hand 1: basal fruit at the top; hand 6: distal hand at the bottom) and only six hands of bananas were used in this study. The experiment was conducted using randomized complete block design with three replications and each individual tree of Rastali banana including 6 hands with 3 fingers per hand was considered as a replication. Data from the measurements of physical (fresh weight, length, diameter, peel and pulp colors, pulp firmness, peel and pulp moisture content and stomatal density), chemical (fruit pH, sugars and organic acids content and tannin concentration), and physiological (respiration rate and ethylene production) quality tests were analyzed using analysis of variance and means separation was carried out using Duncan’s multiple range tests. Regression analysis was carried out to describe the relationship of the physico-chemical characteristics during fruit growth and development. Fruit length and diameter followed a similar trend observed in fruit fresh weight throughout banana development and three physiological stages (S1, S2 and S3) of sigmoid growth were identified. Initially, growth was slowed at S1 which occupied the first 4 weeks of growth where the cells were dividing actively. This followed by rapid growth at S2 (5th to 10th weeks) where cell expansion took place. Growth was constant at S3 (11 and 12 weeks) where the fruits have reached physiological maturity stage. Growth of Rastali banana was further supported by the cellular structure studies using light microscope. Peel cells performed a periclinal growth and was accompanied by an increase in fruit peel and pulp thickness as fruit developed. Peel and pulp colors were expressed in lightness (L*), chroma (C*) and hue (h°). Peel tuned from matured green to yellow during ripening while pulp color became more vivid and yellow as fruit matured and ripened. Peel moisture content decreased as fruit developed and ripened, in contrast,pulp moisture content increased as fruit developed. During fruit growth and development, pulp firmness increased at initial stages of fruit development and thereafter decreased during maturation and fruits soften during ripening. Fruits became more acidic and taste sweeter as fruit matured and ripened. Sucrose, fructose and glucose were the main sugars found in Rastali banana while malic, citric and succinic acids were the main organic acids found in the fruit. In this study, there was no ethylene production detected throughout 12 weeks of fruit development. Ethylene was detected at day 1 after ripening was initiated. Rastali banana was characterized as climacteric fruit with the upsurge of CO2 production coincided with the ethylene production occurred at day 3 after ripening. Peel cells performed a periclinal growth resulted in tangential expansion which led to flattening of the fruit angle when approaching maturation. As fruit developed, parenchymatous cells lose their integrity, lignified fibre degraded at the peel region and starch filled the pulp region. Various shape of starch found at the peel and pulp regions. Starch at the peel was mostly small and granular shape while starch at the pulp was large and flat disc in shape. It is clear that Rastali banana exhibited a sigmoid growth pattern and physico-chemical changes during fruit growth and development. Rastali banana showed physiological maturity at week 11 and 12 after emergence of the first hand with constant fruit growth and fruits are ready to be harvested.